Wokół języka pism wizyjnych św. Hildegardy z Bingen - Wieczorek, Bartosz (Studia Theologica Varsaviensia, 2017)
This article presents the concept of interpretation for an unusual symbolic language of Saint Hildegard von Bingen, who in her writing tried to express the unity of the entire creation and its dependence on the Creator. According to Hildegard, the whole world was planned and ordered by the Creator, and each thing is a kind of message, the word of the Creator, which is related to Him. The disaster, which was the original sin, disrupted the original harmony of the creation and introduced evil and falsehood to this creation. Relationships between earthly things, as well as between God and man were falsified. Thanks to her visions and their interpretations, Hildegard wants to show the real place of man in space. She wants to restore his ability to understand the world and read it as a message and the path to the Creator. Moreover, she intends to clean up the human language from the false. However, Saint Hildegard von Bingen knows quite well that the language without falsehood and lies, which reflects the harmony of man with cosmos and God, will be revealed to man at the end of time. For people, who have contact with Hildegard and for Hildegard, this language is the metaphysical truth, but not a historical reality (yet).